Food court hygiene assessment and food safety knowledge, attitudes and practices of food handlers in Putrajaya - Abdullah, Mohd Firdaus Siau; Radu, Son; Othman, Mohhiddin; Toh, Poh See; Chai, Lay Ching (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
This cross sectional study aimed to explored the pattern of socio-demographic distribution, to assess the level of KAP of food safety; and the relationship with the level of premise cleanliness in the food courts at Putrajaya. Distribution of food handlers socio-demographic profile was Malaysian (62.0%), male (70.4%), working experienced in food industry (82.0%) and attended food handler training (85.0%). The mean age was 28.7 years and 85.4% having income not less than RM 1,500 monthly. 78.5% of the food handlers at educational level were found as primary/secondary school. 15.0% of the respondents had not attended the food sanitation training. The findings reveal that food handlers' KAP were high with a mean percentage score more than 79.0%.The majority of the food courts in Putrajaya had consistently moderate level of cleanliness (63.5%) with the mean of 83.03%. Only 27.4% of the food courts were in the level of clean situation (>89% of premise cleanliness score) and 9.1% were not in the clean condition (<70% of premise cleanliness score).